Diagnóstico socioeconómico de la población de Monte Sinaí, Cooperativa Realidad de Dios, en la ciudad de Guayaquil - Baque Robaños, Allison Demerith (2024)
The economic and social development of a group of people must be aimed at empowering the resources they have, for this reason, the socioeconomic situation of the population of Monte Sinaí, Cooperativa Realidad de Dios, in the city of Guayaquil was analyzed. . Considering inequality from a broad perspective, which goes beyond monetary income, is part of seeing the reality of those sectors that are violated. It is crucial to recognize that development implies not only an increase in income, but also the expansion of life opportunities and alternatives for the population. In this sense, poverty is not only defined by the lack of economic resources, but also by the unmet basic needs and limited access to essential services. The applied research methodology allowed us to provide favorable foundations for the proposal, understanding in depth the different socioeconomic factors, and in the analysis of results, specific needs, challenges and opportunities are identified.